Functional Properties and Promotion Effect on Osteoblastogenic Differentiation of Tuna Bone Collagen Peptides - Guanmiao XIAN; Yijing CAI; Wenhua MIAO; Yufang ZHOU; Shiqi HU; Conghan SHU; Bin ZHENG (Shipin gongye ke-ji)
The study was to investigate the functional properties of tuna bone collagen peptides (TBCP) and their effects on the proliferation, differentiation and mineralization of MC3T3-E1 osteoblasts. TBCP1 and TBCP2 were prepared by enzymolysis. Then the molecular weight distribution, amino acid composition, water holding capacity, water absorption, oil absorption, and emulsification properties of TBCP were analyzed. Moreover, to elucidate the osteogenic activity of TBCP, the cell proliferation rate, the activity of alkaline phosphatase (ALP), the secretion of collagen type I (COL I) and osteocalcin (OCN), as well as the number of mineralized nodules of MC3T3-E1 osteoblasts were analyzed. Besides, the mRNA expression levels of differentiation-related genes of MC3T3-E1were detected using the real-time quantitative PCR. The results demonstrated that the molecular weight of TBCP1 was mainly concentrated below 1000 Da. TBCP1 had better water holding capacity and water absorption, but its oil absorption was poorer than TBCP2. TBCP1 and TBCP2 were both rich in glycine, glutamic acid, prolline and alanine, and had similar amino acid compositions. Compared with the control group, TBCP had no significant inhibitory effect on osteoblast proliferation. The ALP activity of MC3T3-E1 was significantly increased by 100~200 μg/mL TBCP1 and 200 μg/mL TBCP2 (P<0.05). The content of COL I was extremely increased by 50~200 μg/mL TBCP1 and 100 μg/mL TBCP2 (P<0.01). Also, TBCP could promote the secretion of OCN, and the effect was strongly significant when the concentration of TBCP1 was 50 and 100 μg/mL (P<0.01). In addition, 50 and 100 μg/mL TBCP1, as well as 20 and 50 μg/mL TBCP2 significantly promoted the formation of mineralized nodules of osteoblast (P<0.05). Furthermore, 100 μg/mL TBCP1 could significantly up-regulate the expression levels of ALP and COL I genes (P<0.05), while 200 μg/mL TBCP1 increased the expression level of OCN gene remarkably (P<0.05). In conclusion, TBCP has good osteogenic activity, and low molecular weight TBCP1 can promote the proliferation, differentiation and mineralization of MC3T3-E1 better.